PENGEMBANGAN BELAJAR MANDIRI - Pujiriyanto Pujiriyanto (MAJALAH ILMIAH PEMBELAJARAN, 2006)
Self motivated learning has significant potentially in supporting the life long education program. Skills are needed for being an effective learner in self motivated learning. These skills can be developed through instructional process. Teachers must change their control orientation by providing greater to learning autonomy for their learner, allowing with what’s learner think by addressing all the three dimensions such are social, paedagogical and psychological in their learning process. Learner is not programmed individu but exist to create their program themselves. Learner must be taught how to use their metacognitive experiences to find out effective metacognitive strategies. There are many constraints in developing selft motivated learning relate to educational system, academic culture, limited skills and other pre requisite, the learner personal traits and others. Self motivated learning could be incoorporated with the traditional education model. A person who is concern in developing self motivated learning must deliberate from his personal traits by himself. Self awareness is essential factor as entry point to initiate self motivated learning development.